More money for some: The redistributive effects of open market operations - Christian Bustamante (Bank of Canada, 2021)
Using a general equilibrium search-theoretic model of money, I study the distributional effects of open market operations. In my model, heterogeneous agents trade bilaterally among themselves in a frictional market and save using cash and illiquid short-term nominal government bonds. Wealth effects generate slow adjustments in agents' portfolios following their trading activity in decentralized markets, giving rise to a persistent and nondegenerate distribution of assets. The model reproduces the distribution of asset levels and portfolios across households observed in the data, which is crucial to quantitatively assess the incidence of monetary policy changes at the individual level. I find that an open market operation targeting a higher nominal interest rate requires increasing the relative supply of bonds, raising the ability of agents to self-insure against idiosyncratic shocks. As a result, in the long run, inequality falls, and the inefficiencies in decentralized trading shrink. This leads agents that are relatively poor and more liquidity-constrained to benefit the most by increasing their consumption and welfare.
Keywords: E21; E32; E52; 330; Inflation and prices; Monetary policy; Monetary policy implementation; Monetary policy transmission